Corporate Social Responsibility in the Colombian Business Sector During the Covid-19 Pandemic - Galvis Largo, Jinneth Ximena
The situation generated by Covid-19 generated a global crisis and demanded the management of companies to help during that crisis. Among the options to solve problems of this type are Corporate Social Responsibility and marketing programs aimed at compliance, these are Social Marketing and Cause-Based Marketing. Through this research, we sought to identifywhich companies in Colombia have carried out this type of practice and how the business sector was forced to respond to the problems that arose from the pandemic. Methodologically, the search for bibliographic material was carried out to determine whether or not these companies existed and what practices were taken into account before and during the pandemic. Subsequently, the selected articles were reviewed, and based on them, an analysis was carried out that showed that there is indeed a permanent practice of corporate social responsibility of social marketing and with cause. The evidence offers important information about specific actions of companies in Colombia before the pandemic, but it also reveals howthere was a deepening of Corporate Social Responsibility practices in response to the social and economic crisis generated. The conclusions indicate that beyond the requirements of the law and given the interest of the companies to withstand the economic crisis and maintain consumption, there were shifts in behavior that pointed to social welfare